Influence of Inorganic Salts on Soils Liquid and Plastic Limits - Ayininuola, G.M.; Agbede, O.A. (Civil Engineering Dimension, 2013)
This study focused on the influence of inorganic salts on soil liquid limit (LL) and plastic limit (PL). Sodium chloride, NaCl, potassium nitrate KNO3 and calcium sulphate, CaSO4 of various concentrations were added to two subsoils. Their liquid and plastic limits before and after contamination were monitored. Soil cation exchange capacity (CEC), exchangeable cations (sodium, Na+, potassium, K+, and calcium, Ca2+) and exchangeable anions (chloride, Cl-, nitrate, NO3, and sulphate, SO42-) were determined. A set of equations for predicting LL and PL, (with R2 = 0.908 to 0.990) at different levels of chemical interaction with time was developed using multiple regression analysis model. The results showed that both NaCl and KNO3 brought about reduction in LL and PL while CaSO4 addition led to increment in LL and PL. The predictive equations revealed that there is high tendency for the contaminated soils to regain their uncontaminated LL and PL values with time.